2014
DOI: 10.1590/0100-2945-347/13
|View full text |Cite
|
Sign up to set email alerts
|

Custo de produção de goiabas para mesa produzidas com e sem ensacamento: estudo de caso

Abstract: O ensacamento de goiabas para mesa tem por finalidade proteger os frutos contra o ataque de pragas, reduzir a aplicações e os níveis de resíduo de agroquímicos. O objetivo deste trabalho foi avaliar a sustentabilidade econômica da produção de goiabas, por meio da comparação do custo de produção entre os sistemas de cultivo com e sem ensacamento dos frutos. Foi realizado um estudo de caso com dados obtidos de uma propriedade comercial de goiabas para mesa no município de Valinhos - SP. O custo de produção foi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 6 publications
0
5
0
1
Order By: Relevance
“…Guava fruit bagging increases the length, diameter, and mass of the fruit, caused by their metabolic alteration (Tokairin et al, 2014;Azevedo et al, 2016), a behavior that has also been observed in other fruits, such as in the 'Royal Gala','Fuji Suprema','Catarina', apples (Santos et al, 2015). For apples, the white nonwoven fabric bags provided fruits with higher mass and diameter.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Guava fruit bagging increases the length, diameter, and mass of the fruit, caused by their metabolic alteration (Tokairin et al, 2014;Azevedo et al, 2016), a behavior that has also been observed in other fruits, such as in the 'Royal Gala','Fuji Suprema','Catarina', apples (Santos et al, 2015). For apples, the white nonwoven fabric bags provided fruits with higher mass and diameter.…”
Section: Resultsmentioning
confidence: 62%
“…Besides insect control, bagging also influences the post-harvest and quality of the fruit, and may even increase weight, modify fruit color (Tokairin et al, 2014), as well as increase size, humidity, and the contents of vitamin C (Hossain et al, 2018) and soluble solids (Edirimanna et al, 2015;Meena et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The psyllid Triozoida limbata Enderlein 1918 (Hemiptera: Psylloidea: Triozidae) is a critical guava ( Psidium guajava L.) pest in the neotropical region, occurring in Argentina, Bolivia, Brazil, Colombia, Costa Rica, Ecuador, El Salvador, French Guiana, Mexico, Panama, Peru and Trinidad and Tobago (Brown & Hodkinson, 1988; Burckhardt, 1988). Guava orchards are of food importance (due to the nutrients present in their fruits), economic (due to the income generated for farmers) and social (due to the jobs generated) (Acham et al, 2018; Tokairin et al, 2014). These tiny insects, popularly known as jumping plant lice, are monophagous on guava and had minor economic importance until becoming a key pest in commercial orchards (Semeão et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…FIGURA 1: Esquema do processo de venda do produto direto para o varejo (Produtor-Loja) Já os outros 82% da produção foram comercializadas no CEASA -Irajá/RJ com um preço médio de venda de R$1,33/kg, valor inferior, ao obtido no comércio de goiabas no CEAGESP, de R$1,85/kg (TOKAIRIN, 2014). O conjunto de caixas de goiabas comercializado no CEASA, é composto por goiabas do mesmo padrão daquelas comercializadas no sistema de varejo (Produtor-Loja) goiabas de menor tamanho, goiabas maduras e por aquelas que possuem algum tipo de defeito em sua superfície, mas que não compromete o seu consumo, cada classificação separada em caixas distintas.…”
unclassified